NARRATING STUDENTS’ IDENTITY TO PROMOTE CRITICAL LANGUAGE AWARENESS - Arini Nurul Hidayati; Bilal Mohnawawi; Rizal Ramdhani (Getsempena English Education Journal, 2019)
This paper explores the use of students’ narration of their personal and social identity to build their sensitivity towards the language form, use, and context in pedagogical arena. It shows how the students construct their multiple identities when they revealed a simple part of their own life history trajectories in one particular time and how these identities are transformed or conserved as they enter a new discourse community. A narrative analysis is employed to document the students’ identification and negotiation of meaning as a social process in identity formation. The stories reveal three emerging themes showing students’ raising critical language awareness; a strong ethnical identity of Silvani, a Sundanese-Javanese child growing as Betawinese living in Sundanese environment, realising Sonny’s use of code-mixing in many inappropriate contexts, and considering self-belief in Barley’s classroom interaction.